2023
DOI: 10.1002/cam4.6373
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of breast cancer screening: Cohort study of breast cancer mortality and overdiagnosis

Sabrina Wang,
Farhana Sultana,
Anne Kavanagh
et al.

Abstract: BackgroundQuantifying the benefits and harms of breast cancer screening accurately is important for planning and evaluating screening programs and for enabling women to make informed decisions about participation. However, few cohort studies have attempted to estimate benefit and harm simultaneously.AimsWe aimed to quantify the impact of mammographic screening on breast cancer mortality and overdiagnosis using a cohort of women invited to attend Australia's national screening program, BreastScreen.MethodsIn a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Ongoing surveillance to identify newly published studies was conducted through March 2024 to identify major studies published in the interim. Two new nonrandomized studies were identified and are not further discussed, as they would not change interpretation of the review findings or conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing surveillance to identify newly published studies was conducted through March 2024 to identify major studies published in the interim. Two new nonrandomized studies were identified and are not further discussed, as they would not change interpretation of the review findings or conclusions.…”
Section: Methodsmentioning
confidence: 99%